CP-146 Evaluation of an educational programme on oral anticoagulants 3 years after its implementation in a cardiology department. (25th February 2017) - Benbouzid, A; Gauthier, V; Brito, E; Eychennes, N; Chung, C; Profizi, E; terline, D De; Fernandez, C; Cohen, A; Antignac, M
Abstract : Background: In January 2013, a multidisciplinary educational programme, 'ETAP', for patients treated with oral anticoagulants was implemented in our cardiology department. Purpose: To evaluate skills and adherence regarding anticoagulant therapy of patients included in an educational programme. To examine factors associated with poor skills scores. Material and methods: Patients were enrolled in the ETAP programme and received individual education from a multidisciplinary team (dietician, nurse and pharmacist) from January 2013 to February 2016, and those who gave their oral consent were included in this assessment. During hospitalisation, an initial evaluation skill score (E1 score: 0 to 1) was assessed with a specific questionnaire designed by our team. At least 1 month after the educational intervention and discharge from the hospital, patients were called by a trained pharmacy student. Patients were submitted to the same skill questionnaire (E2 score: 0 to 1) and an 8 item Morisky medication adherence scale (MMAS-8). Furthermore, patients were interrogated on the occurrence of haemorrhagic or thrombotic events and INR value at the time of the call. Results: 412 patients were enrolled in ETAP. 27% (365/1336) of patients receiving VKA and 16% (47/286) of patients receiving DOA were educated. Mean skill scores were 0.82 (±0.23) points and 0.81 (±0.18) points for E1 and E2, respectively, and no significant difference (p=0.47) was observed the two. 66% of patients had high level of adherence. Thrombotic and haemorrhagic events were observed in 11% (18/161) of interviewed patients. 58% (93/161) of patients were aware of their INR, and INR was in the target area. The skill score declined with age (p<0.05). Conclusion: Only 16% of patients receiving DOA were educated; most patients did not start DAO treatment in our department and VKA patients were favoured. As the mean E2 skill score assessed was not significantly different from the mean E1 score, patients seem to keep their skills in the long term. 44% of patient had a poor level of adherence. This study underlines the necessity to improve education in elderly patients and in patients treated by DOA. No conflict of interest